Cardiotoxicity of 5-fluorouracil in a young colorectal cancer patient – case report and review of literature - Wysocki, Piotr J.; Hutka, Małgorzata (Archives of Medical Science, 2009)
Pyrimidine analogues such as 5-fluorouracil (5-FU) are widely used in adjuvant and palliative treatment of various solid tumours. However, their administration may be associated with severe adverse events such as myelosuppression, mucositis or cardiotoxicity. Cardiotoxicity is a relatively rare event but its fatal outcomes occur at a rate of 2.2-13.3%. Since 5-fluorouracil is widely used in medical oncology, cardiotoxicity associated with its administration may significantly impair treatment of patients with cancers sensitive to pyrimidine analogues. This article reviews fluoropyrimidine-associated cardiotoxicity and presents a case report of a young woman who experienced this complication during 5-fluorouracil treatment.